National Security and Democracy on the Internet in Israel: - Dahan, Michael (Javnost-The Public, 1999)
There exists an inherent conflict of values in Israeli society -- the primacy of national security, which subordinates almost every other aspect of democracy in Israel, versus the ideal of liberal democracy focusing on individual rights -- chief among these being freedom of expression. These conflicting values have been brought to the surface in recent years due to the rapid growth of Internet use by the general public in Israel. The incidents reviewed in this paper serve to underscore the tensions between national security and democracy in Israel, a tension that today is related more to deeply-seated political and cultural concepts of democracy than to any real threat to the country's existence. This paper discusses the political and cultural aspects of democracy and national security in Israel vis-a-vis computer-mediated communication (CMC).